2007
DOI: 10.1038/sj.cdd.4402154
|View full text |Cite
|
Sign up to set email alerts
|

Atypical, bidirectional regulation of cadmium-induced apoptosis via distinct signaling of unfolded protein response

Abstract: Cadmium is a widely distributed nephrotoxic metal that causes renal tubular injury. In this report, we investigated involvement of endoplasmic reticulum (ER) stress and individual unfolded protein responses in cadmium-initiated apoptosis of tubular epithelial cells. Cadmium chloride (CdCl 2 ) induced expression of endogenous ER stress markers, GRP78, GRP94 and CHOP in vitro and in vivo, and subsequently caused cytological changes typical of apoptosis. Attenuation of ER stress by transfection with ER chaperone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 40 publications
5
100
1
Order By: Relevance
“…32 In general, however, the PERK pathway is considered pro-survival, whereas the IRE1 pathway is regarded pro-apoptotic. 3,4,33 From this viewpoint, the pharmacological of 3 0 -deoxyadenosine should be advantageous for blockade of ER stress-induced cell injury. Indeed, we demonstrated in this report that in vivo administration with 3 0 -deoxyadenosine suppressed ER stress-induced activation of the IRE1-JNK pathway, induction of CHOP and consequent apoptosis in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In general, however, the PERK pathway is considered pro-survival, whereas the IRE1 pathway is regarded pro-apoptotic. 3,4,33 From this viewpoint, the pharmacological of 3 0 -deoxyadenosine should be advantageous for blockade of ER stress-induced cell injury. Indeed, we demonstrated in this report that in vivo administration with 3 0 -deoxyadenosine suppressed ER stress-induced activation of the IRE1-JNK pathway, induction of CHOP and consequent apoptosis in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described before. 33 Primary antibodies used were anti-caspase-3 antibody, anti-phospho eIF2a (Ser51) antibody, anti-c-Jun antibody and anti-phospho c-Jun (Ser63) antibody from Cell Signaling (Beverly, MA, USA); and anti-PERK antibody, antiphospho PERK (Thr981) antibody, anti-eIF2a antibody and anti-ATF4 (CREB-2) antibody from Santa Cruz Biotechnology (Santa Cruz, CA, USA). As a loading control, levels of b-actin and lamin B1 were evaluated using anti-b-actin antibody (Sigma-Aldrich Japan) and anti-lamin B1 antibody (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…28 In general, however, the PERK and the ATF6 pathways are considered pro-survival, whereas the IRE1 pathway is regarded pro-apoptotic. [29][30][31][32] A selective inhibitor of the IRE1 pathway should, therefore, have an advantage for the treatment of ER stress-related disorders. Indeed, in the present report, we showed that in vivo administration with rapamycin markedly suppressed ER stress-triggered activation of the IRE1-JNK pathway and consequent apoptosis in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that disruption of intracellular calcium homeostasis is one of the primary processes in the early development of cell injury [1][2][3] [19,[24][25][26][27][28]. In summary, ER homeostasis is a fragile equilibrium, which can be modulated by dysregulation of calcium or oxidative/reductive balance, features previously associated with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%